1969
DOI: 10.1103/physrev.186.5
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Cross Sections ofO2andO4between 2000 and 2800 Å

Abstract: The total absorption of radiation in the 2000-2800 A region has been measured for 0 2 . The absorption does not follow Beer's law. The linear increase in the measured effective absorption cross section with rise in gas pressure is ascribed to the absorption caused by 0 4 . With methods developed and presented recently by the writer, the absorption cross sections of 0 2 and 0 4 are derived from total absorption measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The nature of the Wulf bands whose intensity is proportional to the square of the pressure is still controversial: They are attributed either to the 04 dimer, to the (02) 2 collision complex or to collision-induced absorption (CIA) [19][20][21][22].…”
Section: The Wulf Bandsmentioning
confidence: 99%
“…The nature of the Wulf bands whose intensity is proportional to the square of the pressure is still controversial: They are attributed either to the 04 dimer, to the (02) 2 collision complex or to collision-induced absorption (CIA) [19][20][21][22].…”
Section: The Wulf Bandsmentioning
confidence: 99%
“…Subsequently the O 2 complex was studied at lower temperatures, 4 while some weak absorption phenomena in the 200 -280-nm UV range were also observed. 5 By now the ͑O 2 ͒ 2 absorptions are well characterized, and pressure-dependent cross sections have been derived through the work of Dianov-Klokov, 6 Greenblatt et al, 7 and recently Newnham and Ballard. 8 The collisional complexes relate to an O 2 -O 2 interaction potential, and the broad absorption features observed at room temperature correspond to continuum states at positive energies.…”
Section: Introductionmentioning
confidence: 99%
“…4,10,11 On the basis of measurements of pressure-dependent absorption in pure oxygen, Shardanand estimated the value of the absorption cross section of the O 2 -O 2 pair to be about 1000 times higher than the cross section for free O 2 molecules. 12 Studies of a wide range of X partners in an X -O 2 collision pair 4,10,11 have shown that intermolecular interactions can enhance the O 2 absorption by values up to 10 6 -10 7 . These studies have shown that the ionization potential of the X partner, IP X , is the main factor determining the degree of enhancement in the UV region of the spectrum.…”
Section: Introductionmentioning
confidence: 99%